2017
DOI: 10.1038/mp.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Preventing intrusive memories after trauma via a brief intervention involving Tetris computer game play in the emergency department: a proof-of-concept randomized controlled trial

Abstract: After psychological trauma, recurrent intrusive visual memories may be distressing and disruptive. Preventive interventions post trauma are lacking. Here we test a behavioural intervention after real-life trauma derived from cognitive neuroscience. We hypothesized that intrusive memories would be significantly reduced in number by an intervention involving a computer game with high visuospatial demands (Tetris), via disrupting consolidation of sensory elements of trauma memory. The Tetris-based intervention (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
270
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(286 citation statements)
references
References 54 publications
(72 reference statements)
7
270
3
6
Order By: Relevance
“…Two recent studies have demonstrated that playing Tetris can effectively reduce intrusions in a clinical setting (Horsch et al, 2017; Iyadurai et al, 2017), highlighting the clinical relevance of playing Tetris shortly after experiencing actual trauma. Our findings are more sobering, and may also reflect a common phenomenon in intervention research, when a new intervention is proposed and tested, with the first studies showing large effects but later studies are much less positive (Ioannidis, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have demonstrated that playing Tetris can effectively reduce intrusions in a clinical setting (Horsch et al, 2017; Iyadurai et al, 2017), highlighting the clinical relevance of playing Tetris shortly after experiencing actual trauma. Our findings are more sobering, and may also reflect a common phenomenon in intervention research, when a new intervention is proposed and tested, with the first studies showing large effects but later studies are much less positive (Ioannidis, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown that playing Tetris on a computer or Nintendo DS can be effective in a clinical setting (Horsch et al, 2017; Iyadurai et al, 2017), such equipment is not always readily available (e.g. in developing countries, during a natural disaster).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to these analogue studies, accumulating evidence suggests that already consolidated distressing autobiographical memories can lose their vividness and emotionality when the individual repeatedly executes guided eye movements whilst remembering [13,14]. Based on these findings, many clinicians and researchers are hopeful that a disruptive effect on intrusive trauma memories can be exploited in effective treatment and preventive interventions for trauma victims (e.g., [15,16,17]).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, through eye movements (like in EMDR) and computer games like Tetris (which has recently translated into populations, e.g. Iyadurai, et al [72], Horsch, et al [73]), a considerable gain has been demonstrated with intrusive suicidal images.…”
Section: Treatment Of Intrusive Imagesmentioning
confidence: 99%